Ectoparasites of Rodents Captured in Bandar Abbas, Southern Iran - EB Kia; H Moghddas-Sani; H Hassanpoor; H Vatandoost; F Zahabiun; AA Akhavan; AA Hanafi-Bojd; Z Telmadarraiy (Tehran University of Medical Sciences, 2009)
Background: Rodents play important role as host of ectoparasites and reservoir of different zoonotic diseases. The aim of this study was to asses the infestation of commensal rodents with ectoparasites in Bandar Abbas, a port city located in the northern part of the Persian Gulf in Iran. Methods: Rodents were captured using live traps during the study period in year 2007. After transferring the rodents to the laboratory, they were identified and then their ectoparasites were collected and mounted for species identification using appropriate systematic keys. Results: A total of 77 rodents were identified including Rattus norvegicus (74%), R. rattus (16.9%), Mus musculus (7.8%) and one hamster. Among all rodents, 40.3% were found infested with ectoparasites. A total of 69 ectoparasites were collected comprising flea, lice, mite and tick. Two species of fleas; Xenopsylla cheopis and X. astia were identified with higher index of X. astia. Two genera of ticks including Hyalomma sp. and Rhipicephalus sp. were identified. Laelaps nuttalli was the only mite found. The Polyplax spinulosa was considered as lice ectoparasite. Conclusion: Among all arthropods collected, flea and lice had the most and the least frequency, respectively. Nearly all rodent species were infested with Xenopsylla. These fleas are important due to their role in plague and murine typhus transmission. Ticks are important due to their role in CCHF (Crimean-Congo Hemorrhagic Fever), theileriosis, babesiosis, anaplasmosis and ehrlichiosis transmission .Monitoring of ectoparaiste infestation is important for preparedness and early warning preparation for possible control of arthropod-borne diseases.